Caffeine Consumption among Various University Students in the UAE, Exploring the Frequencies, Different Sources and Reporting Adverse Effects and Withdrawal Symptoms - Zelal Kharaba; Nour Sammani; Samar Ashour; Rose Ghemrawi; Ahmad Z. Al Meslamani; Ahmad Al-Azayzih; Manal Ali Buabeid; Yassen Alfoteih (Journal of Nutrition and Metabolism)
Background. Caffeine is widely consumed among students due to its cognitive and physical enhancing effects. However, little is known about the consumption pattern of different caffeinated products among university students in the United Arab Emirates (UAE). Aim. To investigate the frequency of caffeine consumption among the young population of students, assess types of caffeinated products consumed, and document adverse effects and withdrawal symptoms experienced by university students. Methods. A cross-sectional study was conducted in the UAE from December 2019 to March 2020. A random sample of 500 university students from different universities in the UAE were approached and asked to complete a self-administered online-based questionnaire. Data were analyzed using the Statistical Package for Social Science (SPSS) version 26. Results. Of (n = 500) surveyed students, (n = 467) completed the survey 93.4%. The average level of caffeine consumption was significantly higher in females compared to male students (p<0.005). Coffee was the highest favored source of caffeine (67.7%) followed by tea (47.3%). The average daily intake of caffeine was found to be 264 mg/day. Surprisingly, almost a third of students reported a high level of daily consumption (>400 mg/day) and more than half of them consumed less than 199 mg/day. Large proportions of students 91.1% have their caffeinated beverage after or while eating meals and 42.8% considered that this habit helped in avoiding acid reflux. Interestingly, around one third of participants have poor knowledge of caffeine-containing medical products, which seemed to affect the level of consumption in the student population (p<0.05). The highest reported reason for caffeine intake was for studying purposes (59.4%). Conclusion. Caffeine consumption is highly prevalent among university students in the UAE. Yet, there is insufficiency in the current knowledge of safe caffeine consumption patterns reflecting the importance of health awareness programs and nutritional lectures to decrease the long-term health issues and unintentional overdose of caffeine.